2021
DOI: 10.1021/acschembio.1c00568
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds of Arthrospira spp. (Spirulina) with Potential Anticancer Activities: A Systematic Review

Abstract: Arthrospira, a genus of blue-green cyanobacteria, is known for its great biological activity due to the presence of a large number of substances that are potentially active against tumor cells. This review aimed to evaluate the potential of Arthrospira spp. for the treatment or reduction of several types of cancer, in addition to elucidating the mechanism of action by which their compounds act on tumor cells. A systematic review was carried out in PubMed, Science Direct, LILACS, and SciELO databases, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Phycocyanin exhibits a wide range of beneficial biological activities stemming from its antioxidant, anti‐inflammatory, and anticancer properties, in addition to various hepato‐, nephro‐, and cardioprotective properties [1–4] . Some studies have reported that phycocyanin has antibacterial activity against drug‐resistant bacteria [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Phycocyanin exhibits a wide range of beneficial biological activities stemming from its antioxidant, anti‐inflammatory, and anticancer properties, in addition to various hepato‐, nephro‐, and cardioprotective properties [1–4] . Some studies have reported that phycocyanin has antibacterial activity against drug‐resistant bacteria [5] .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, microalgae have been widely used in the fields of food, biofuels, health products and environmental control [ 56 , 57 ]. Recently, microalgae have been of considerable use in biomedical fields for applications such as bioanalysis, tissue engineering, drug delivery and tumor therapy, and they exhibit high biocompatibility both in vivo and in vitro [ [58] , [59] , [60] ]. Studies by Woo et al.…”
Section: Oxygen Shuttles Produced Oxygen For Enhanced Tumor Therapymentioning
confidence: 99%
“…Cyanobacterial natural products still seem to prevail followed at much lesser proportions by alkaloids, aromatic compounds, cyclic depsipeptides, cyclic peptides, cyclic peptide, cyclophane, fatty acids, linear peptides, lipopeptides, nucleosides, phenols, macrolides, polyketides, polyphenyl ethers, porphinoids and terpenoids [51]. These interesting and biochemically active compounds possess biological activity covering a wide range of antibacterial [52][53][54][55], antifungal [56], antialgal [56], antiviral [57], anticancer effectiveness [58][59][60], and immunosuppressive [61] activities. Some bioactive lead compound are bastadin, bis-x-butyrolactone, hapalindole, didehydromirazole, kawaguchipeptin B, muscoride, noscomin, nostocine A, scytophytin, and lipids [62] exhibited with antibacterial activity and, ambiguines, calothrixin, cyanobacterin, fischerindole A, hapalindole, hassallidin, phytoalexin, scytophycin, tjipanazole and Y-lactone [63,64] with antifungal activity and few compound such as 4,4′-dihydroxybiphenyl, norhamane pyrido (3,4-b)indole, beta-glucan, bacteriocin, ambiguines, parsiguine, scytoscalarol, hapalindole [65] which have been reported to show antimicrobial activity.…”
Section: Bioactive Compounds From Cyanobacteriamentioning
confidence: 99%